Sustainable Use of Orange Peel Essential Oil: A Natural Antioxidant to Combat Fish Oil Oxidation - Erol, Hüseyin Serkan; Metin, Hilal; Kaynar, Özgür; Acar, Ümit; Kesbiç, Osman Sabri (Kastamonu University, 2024)
This study examines the protective effects of orange peel essential oil (OEo) against the oxidation of fish oil and its prospective application as an antioxidant. The investigation involved the addition of varying ratios of OEo (100 ppm-1600 ppm) to fish oil, and the protective effects against oxidation were assessed using measurements of peroxide value (PV) and malondialdehyde (MDA) generation. The accelerated oxidation test was conducted at a temperature of 55°C, 70% humidity, and continuous light for a duration of 120 hours. Furthermore, statistical disparities among the experimental groups were examined. The results indicated considerably reduced levels of PV and MDA (p
Keywords: Animal Nutrition; Hayvan Beslenmesi; Orange Peel Essential Oil; Fish Oil Oxidation; Natural Antioxidants; Lipid Peroxidation; Sustainable Antioxidants; Portakal Kabuğu Esansiyel Yağı; Balık Yağı Oksidasyonu; Doğal Antioksidanlar; Lipid Peroksidasyonu; Sürdürülebilir Antioksidanlar